Analisis Kearifan Lokal dan Nilai Pendidikan Karakter pada Novel Pasar Karya Kuntowijoyo - Diana Naibaho; Marlina Agkris Tambunan; Monalisa Frince Sianturi (Medan Resource Center, 2022)
This thesis discusses the analysis of local wisdom and the value of character education in the novel